Characterization and Analysis of Open Brazilian Judiciary Data - Seufitelli, Danilo B.; Mata, Weverton R. R.; Souza, Rafael C.; Brandão, Michele A.; Moro, Mirella M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
Govern transparency is widely accepted as an effective democratic process in many countries. In Brazil, the information-access law contributes to public administration transparency, as public data is available on the Web. However, such data are in different formats and not standardized, which makes it difficult to obtain information, mainly in an automated way. Hence, this work presents an enrichment methodology for an existing open Brazilian judiciary database, a characterization of the available data, and an analysis of the data about judiciary professionals and their earns. The results reveal a lack of linear correlations between the high salaries and their personal benefits. Also, there is a discrepancy between Judiciary salaries and advantages through Brazilian regions, which may be explained by the higher living costs in some regions. Finally, our study reveals the administrative Brazilian Judiciary data do not conform to all Open Government Data principles, and the enriched database helps to solve such problems.